Improved GaN films with low background doping and low deep trap density grown by hydride vapor phase epitaxy. Issue 4 (18th March 2015) - Polyakov, Alexander; Smirnov, Nikolai; Govorkov, Anatoli; Kozhukhova, Elena; Yugova, Tatiana; Usikov, Alexander; Helava, Heikki; Makarov, Yuri
Abstract: Electrical properties and deep electron and hole traps spectra are compared for undoped n‐GaN films grown by hydride vapor phase epitaxy (HVPE) on sapphire substrates at 850 °C (Group 1) and 950 °C (Group 2). Group 1 samples have very low residual donor concentration ((2‐5)×10 14 cm ‐3 ), very low density of electron and hole traps, low leakage current of Schottky diodes. Group 2 samples are not very different from the usual thick HVPE samples in terms of predominant electron and hole traps and MCL spectra. But the concentration of both electron and hole traps is quite high and could contribute to rather high reverse leakage current, low photocurrent and pronounced tunneling. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)